Evaluation of the Production Capacity: Soup Mixing, Sub Manufacturing Production Department ABC Company - Khate C. Montederamos, Sarah (International Journal of Engineering and Technology, 2019)
Â In the fast pace of today, the consumer market continues to search for easy, fast and satisfying meals, and cup noodles is one of them. The ABC Company is an industry that pioneers in creating these said to go meals and what makes the noodles taste great, it is the flavoring where as in the industry termed soup mix. Made at the sub-manufacturing department of the plant, the soup mixing section is an area for continuous improvement. This study aimed to evaluate the production capacity of the said section. It was discovered via TMS that 40% of the production capacity was not utilized. Operation Standard Time was established at 1 hour and 30 minutes. Thus the best course of action is to change the former 3 batch quota per shift to a 4-5 batches per shift, removing batch if there would be a change flavor in schedule. With the current year plan the operations direct labor cost would save 25% for a 4 batch per shift quota and 40% savings for a 5 batch per shift quota. Other recommendations such as improving PPE used by laborers, reevaluating operation procedures, lining drums with limit lines and automating the process was also suggested. Overall, many aspects of the section could be improved and suggestions stated could be done in the discretion of the company.Â